Mass Education from the War of 1870 to the War of 2001 - Clifford Falk (Adult Education Research Conference, 2002)
This work traces the involvement of the social practice termed education, especially in its lifelong form, to the production of war from the Franco-Prussian War of 1870-71 to the War on Terrorism 2001-____.